Development Instructional Media Based on Virtual Reality Assisted by The MilleaLab Application on Tourism Resources Material - Ningsih, Mega Prani; Novitasari, Nastiti; Ramadhan, Ilham Rohman; Nurdianti, Raden Roro Suci; Shaari, Mohammad Zohir Bin Ahmad; Hannah, Beth; Durgaryan, Alesa (International Journal of Social Learning (IJSL), 2025)
VR technology is changing the world of education by providing immersive and interactive learning experiences. This study develops LaViGeo, a VR-based learning media designed using the MilleaLab application to enhance learning in tourism resource materials. This study follows the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. This study involved 21 students in the Geography of Transportation and Tourism course, selected randomly. Data were collected using a validation questionnaire for material and media experts, as well as a student response survey. The results is LaViGeo was very feasible and effective to use from expert assessments and through trials with students. The integration of multimedia elements, learning videos, 360-degree images and interactive features can be accepted by students for concept materials related to tourism geography. There are challenges in the form of direct integration of 360-degree YouTube videos and limited trials so that further research is needed regarding wider implementation and optimization.